Social comparison; gender analysis, social media accounts, and instagram followers - Sigit Muryono; Ifdil Ifdil; Yuda Syahputra; Itsar Bolo Rangka; Kadek Suranata (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The use of social media is a popular communication tool for children and adolescents, but many adults also use it. This is because the fastest source of information today is social media, but from the many benefits there are also impacts that occur, students become less confident in their social environment, this condition is caused by social comparison, often comparing themselves with others when looking at the status of their friends. This study aims to analyze the conditions of social comparison of students based on gender, number of social media accounts, number of smartphones and number of Instagram followers. This research is a quantitative descriptive study obtained through random sampling. The sample in this study were 213 students from Madrasah Aliyah in Jakarta. Data was collected using the Social Comparison Scale (SCS) with 26 items in a five-point response format. The analysis technique used the item response theory (IRT) approach with the Rasch Model analysis. This research tested descriptive with the help of WINSTEPS Version 4.7.0. The results show that the social comparison tendency of Madrasah Aliyah students in the city of Jakarta is more towards positive social comparison or towards positive behavior, for example students more often compare their own achievements with their friends. In addition, students will more often compare themselves with others if they often see the status of friends who have joined to become their Instagram followers.